Putevoditel' / Gosudarstvennyj archiv Rossijskoj Federacii = . A research guide / State Archive of the Russian Federation (Blagovest [etc.])
1: Fondy Gosudarstvennogo archiva Rossijskoj Federacii po istorii Rossii XIX-načala XX vv. = Collections of the State Archive of the Russian Federation on the history of Russia in the 19th and early-20th centuries / red.: S.V. Mironenko, Gregori L. Friz.